Nasoalveolar Moldıng And Presurgıcal Orthopedıcs In Unılateral Clefts Of The Lıp, Alveolus And Palate - Part 1 - - Ayşe Tuba Altuğ; Barry Grayson; Court Cutting (Turkish Journal of Orthodontics, 2004)

(untitled)
The purpose of this review are to present the alveolar and nasal molding technique that reduces the severity of the deformity and helps to achieve better and more stable results after the primary lip closure operation in unilateral cleft lip and palate babies.